Medical practices in the context of socio-cultural transformations - M.-M. Lyubivaya (Ukrainian Cultural Studies, 2021)
The article is devoted to revealing the place and significance of therapeutic practices, which are a significant component of cultural practices and undergo transformation in accordance with the changing picture of the world and the dominant narrative of culture. Regardless of the level of development of society, the problem of Health is a priority, and a set of practices and ideas designed to preserve it is a sustainable element of any culture. Socio-cultural conditions of the present make clear the relevance of the concepts of "Health" and "disease", demonstrate the influence of medical practices and ideas about them on all spheres of human existence, but at the same time there is an insufficient level of scientific understanding of the formation and translation of narratives related to the purpose and participants of therapeutic communication, the principles of its functioning, which determines the importance of research on this topic within the framework of cultural discourse. The scientific novelty of the work consists in determining the mutual influence of medical practices and various forms of cultural text, identifying the experience of treating the disease in its specific historical and cultural existence, as well as its projections in linguistic and mythological systems. In the study of the above-mentioned issues, the method of cultural and historical reconstruction is applied, which reveals the formation and development of medical discourse and communication and attempts to rationalize and legitimize them in the cultural space.